2019
DOI: 10.1002/hep.30658
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Weight Loss Medications Into Hepatology Practice for Nonalcoholic Steatohepatitis

Abstract: There is an urgent need for practical approaches to patients with nonalcoholic steatohepatitis (NASH). Total body weight loss (TBWL) is an important approach, as its effects are amplified in the liver, with 10% TBWL resulting in a 50% loss of liver triglycerides and improvement in all aspects of NASH histology. Lifestyle changes are the first step in addressing TBWL, but uncommonly result in the range required to improve liver histology in NASH (7%-10%). Weight loss medications (WLMs) are an effective addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The main strategy to treat NAFLD focuses on the control of underlying risk factors like diabetes, hyperlipidaemia, obesity and other comorbidities. Since no effective pharmacological treatment for NAFLD/NASH has been approved, the lifestyle changes, consisting of balanced diet and physical activity represent the cornerstone of intervention for NAFLD treatment 132 …”
Section: Lifestyle Intervention In Nafld/nash Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main strategy to treat NAFLD focuses on the control of underlying risk factors like diabetes, hyperlipidaemia, obesity and other comorbidities. Since no effective pharmacological treatment for NAFLD/NASH has been approved, the lifestyle changes, consisting of balanced diet and physical activity represent the cornerstone of intervention for NAFLD treatment 132 …”
Section: Lifestyle Intervention In Nafld/nash Patientsmentioning
confidence: 99%
“…Since no effective pharmacological treatment for NAFLD/NASH has been approved, the lifestyle changes, consisting of balanced diet and physical activity represent the cornerstone of intervention for NAFLD treatment. 132 Recent studies have reported that a 6-to 12-month widespread lifestyle modification, based on reduced energy intake and increased physical activity, leads to improvement in liver enzymes and metabolic parameters, and reduced steatosis and necroinflammation, including ballooning and fibrosi. The most recent European and American guidelines recommend that lifestyle interventions should be included as part of the clinical care of all NAFLD patients, regardless of the stage of disease.…”
Section: Life S T Yle Interventi On In Nafld/ Na S H Patientsmentioning
confidence: 99%
“…31 32 Other scholars have also associated the rising obesity rate with the simultaneous rise in the prevalence of MAFLD. 18 33 34 However, a growing body of literature has pointed out that weight loss can prevent MAFLD from progressing to more serious fatty hepatitis and liver cirrhosis, or even completely reverse the condition, [35][36][37] which has attracted our attention. Combining our outcomes with the results of the aforementioned studies, we have concluded that new strategies are necessary to effectively curb the further spread of MAFLD.…”
Section: Pointed Out Thatmentioning
confidence: 99%
“…An aspect of weight loss that has yet to be widely studied in NAFLD patients is the effects of pharmacologic weight loss agents in the reduction of liver fat content. These drugs can help patients lose 7–10% of their total body weight, fitting well with the amount of weight loss shown needed to improve liver histology in NASH 26,27. One of the criteria to be placed on pharmacologic weight loss agents includes a BMI of greater than 27, a criterion in which 85% of the NASH patients qualify.…”
Section: Non-pharmacologic Therapymentioning
confidence: 85%